Nutrition interventions implemented in hospital to lower risk of sarcopenia in older adults: A systematic review of randomised controlled trials. Issue 1 (5th February 2020) - Rus, Grace E.; Porter, Judi; Brunton, Alexandra; Crocker, Meghan; Kotsimbos, Zoe; Percic, Jessica; Polzella, Louise; Willet, Natasha; Huggins, Catherine E.
Abstract: Aim: There is no standardised interventional approach to preventing or treating sarcopenia in older adults in hospital. The aim of this review was to systematically identify and synthesise the effects of nutritional interventions on markers of sarcopenia in hospitalised patients aged 65 years and older. Methods: Four databases were searched using terms for intervention, population and setting. Eligibility screening of title and abstract and then full‐text papers was competed in duplicate, independently. The final included papers were assessed for quality, and outcome data extracted independently and in duplicate. Outcome data were synthesised by meta‐analysis, where possible, or narratively. Results: Seven hundred and thirty‐two articles were screened for eligibility yielding six studies for inclusion. All studies provided oral nutritional support that aimed to increase protein intake ranging from an additional 10 to 40 g/d, each with a unique formulation of amino acids and/or micronutrients; three studies combined nutritional intervention with an enhanced physical activity program. Five studies measured hand grip strength, the mean difference was 1.97 kg (95% CI 0.55‐3.39, P = .006) greater in the intervention group (n = 166) compared with control group (n = 165). Assessment of muscle mass and activities of daily living were heterogeneous and the changes inconsistent between studies. Conclusions: Few studies inform nutritional management of inpatients with sarcopenia or at risk of sarcopenia. High quality, large intervention trials are needed urgently to identify the optimal nutrition and physical activity intervention combinations to manage sarcopenia in older hospitalised adults. These studies need to include outcome measures of physical function and muscle quality.